Thermoplastic Feeding Appliance - Tamer Türk; Fethiye Çakmak (Galenos Yayinevi, 2006)
A newborn male, aged 5 days, was referred to our clinic with the complaint of nasal regurgitation during bottle feeding. An isolated cleft soft palate was observed during intraoral examination. To assist feeding, the use of a feeding appliance was planned. A feeding appliance was constructed from soft and hard thermoplastic materials. The thermoplastic appliance facilitates feeding and was easily tolerated. Gag reflex was not observed although the appliance extended posteriorly. The patient achieved the desired weight gain sufficient for general anaesthesia within twelve weeks.